Identification of Hydrocarbon Prospect Zones in The AI-1 Well, The Central Sumatra Basin - R. C. Wibowo; A Irawan; O. Dewanto (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2026)
The Central Sumatra Basin is one of the largest hydrocarbon producing back arc basins in Indonesia. Determining the hydrocarbon prospect zone in this basin uses the well logging method and petrophysical analysis which is carried out to determine rock physical parameters such as shale volume, porosity, water saturation, net reservoir and net pay in the Menggala Formation and Pematang Formation as well as to validate the hydrocarbon content so that a value can be obtained. net (net pay) which is able to describe the thickness of the reservoir. In this research, 4 hydrocarbon prospect zones were found in the Menggala Formation at a depth of 5962.32-6125.03 feet and in the Pematang Formation there were 5 hydrocarbon prospect zones at a depth of 6142.39-6444.12 feet. In the Menggala Formation, the physical parameters of the reservoir rock were obtained, namely shale volume values of 15.1%-24.7%, porosity of 15.84%-18.07%, and water saturation of 29.15%-35.18. Meanwhile, in the Pematang Formation, the physical parameters of the reservoir rock were obtained, namely shale volume values of 4.13%-21.72%, porosity of 16.93%-19.04%, and water saturation of 28.83%-34.04%. These two formations have good quality porosity and the fluid type is gas. Based on the final results of the petrophysical analysis, it can be seen that the prospect zone in the Menggala Formation and Pematang Sumur AI-1 Formation of the Central Sumatra Basin as a whole is a hydrocarbon zone. This is because most prospect zones have a net gross value close to 1.